Crime Prediction Using Machine Learning and Deep Learning - P. Karthik,; P. Jayanth,; K. Tharun Nayak,; K. Anil Kumar, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The utilization of machine learning and deep learning methods for crime prediction has become a focal point for researchers, aiming to decipher the complex patterns and occurrences of crime. This review scrutinizes an extensive collection of over 150 scholarly articles to delve into the assortment of machine learning and deep learning techniques employed in forecasting criminal behaviour. It grants access to the datasets leveraged by researchers for crime forecasting and delves into the key methodologies utilized in these predictive algorithms. The study sheds light on the various trends and elements associated with criminal behaviour and underscores the existing deficiencies and prospective avenues for advancing crime prediction precision. This thorough examination of the current research on crime forecasting through machine learning and deep learning serves as an essential resource for scholars in the domain. A more profound comprehension of these predictive methods will empower law enforcement to devise more effective prevention and response strategies against crime.
Keywords: Machine Learning; Deep Learning; Research Review; Crime Prediction; Algorithm Application; Dataset Analysis; Trend Identification; Criminal Activity Factors; Predictive Accuracy; Future Directions; Law Enforcement Strategies